2017
DOI: 10.1091/mbc.e16-07-0485
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of RNA interference and retrotransposons accompany acquisition and evolution of transposases to heterochromatin protein CENPB

Abstract: Fission yeast have adapted to retrotransposon invasion by RNAi-mediated silencing, which has coevolved into a mechanism involving CENPB-mediated heterochromatinization together with ablation of RNAi components via accumulation of recombinogenic repeats in recently diverged species of Schizosaccharomyces. Similar trends are seen in the metazoans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…These proteins, together with CTCF, a master regulator of transcription, would allow the cell to have a wide-ranging stress response, which we speculate may include chromatin remodeling. It is interesting to point out that the TNRC6 family contains homologies to domains of the Schizosaccharomyces pombe Tas3 and Chp1 proteins, which are part of the RNA-induced transcriptional silencing complex ( 55 ). Further investigation is needed, however, to confirm the existence and validity of this model as a general cell stress response mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins, together with CTCF, a master regulator of transcription, would allow the cell to have a wide-ranging stress response, which we speculate may include chromatin remodeling. It is interesting to point out that the TNRC6 family contains homologies to domains of the Schizosaccharomyces pombe Tas3 and Chp1 proteins, which are part of the RNA-induced transcriptional silencing complex ( 55 ). Further investigation is needed, however, to confirm the existence and validity of this model as a general cell stress response mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the DNA-binding domain, CENP-B and pogo share a signature protein region referred to as the DDE endonuclease domain. The DDE endonuclease domain is defined by three carboxylate-containing amino acids (aspartate/D, glutamate/E), precisely located within a 200 aa stretch and believed to be critical to the DNA cleavage activity of transposases [67][68][69]. While the DDE endonuclease domain is common in DNA transposases and retrotransposases/retroviruses, the pogo iteration is unique enough to define a specific family of transposase genes [70].…”
Section: Structure and Origin Of Cenp-bmentioning
confidence: 99%
“…While the DDE endonuclease domain is common in DNA transposases and retrotransposases/retroviruses, the pogo iteration is unique enough to define a specific family of transposase genes [70]. Phylogenetic analyses by several teams have found that this pogo-like gene family, including CENP-B, is evidence of evolutionary domestication [69,[71][72][73]. Many of these gene products have additional homology with CENP-B over the DNA-binding domain [69,73].…”
Section: Structure and Origin Of Cenp-bmentioning
confidence: 99%
“…It is important to note that while Ago1 is evolutionarily conserved, Chp1 and Tas3 are not; in fact, the related fission yeasts Schizosaccharomyces octosporus and S. cryophilus have a truncated Chp1 protein that does not localize to heterochromatin [89], and Tas3 is only found in S. pombe and S. japonicus [82]. However, Tas3 possesses a GW-rich domain, a feature that is conserved in Argonaute interactors, including GW182 proteins in mammals, Gawky in Drosophila, AIN-1 in C. elegans, RNA polymerase IV and RNA polymerase V in Arabidopsis [90,91], suggesting a case of functional conservation rather than conservation at the primary sequence level, with Argonaute as the catalytic component of the complex.…”
Section: Rna Interference-mediated Heterochromatin Formation In Fissimentioning
confidence: 99%